การพัฒนาโมเดลการวัดทักษะชีวิตและอาชีพของนักเรียนระดับชั้นมัธยมศึกษาตอนปลายในศตวรรษที่ 21 - ชนัดดา เทียนฤกษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The research has 3 objectives: 1) to develop and validate of measurement model of life and career skills of upper secondary school students 2) to compare the average of score of the measurements of life and career skills between genders and education programs of upper secondary school students and 3) to establish norms of measurement the life and career of upper secondary school students.The samples are 397 students in mattayom 5 in Bangkok.The data was collected using multi-stage sampling.The research instrument was a scenario questionnaire of life and career skills and it had 3 choices.The collected data was analyzed using descriptive statistics and inferential statistics with t-test, one –way ANOVA, confirmatory factor analysis and normalized T–score. The research findings were as follows: (1) The measurement model of life and career skills was a construct validity, it had chi-square=2.30, df=2, p-value=0.32, GFI=0.99, AGFI=0.99, RMR=0.001, RMSEA=0.04. (2) Female students had a higher mean score for interpersonal and management skills than male students at a statistically significant level of .05. Male and female students had similar communication and problem solving skills. Mathematics-English program had a higher mean score for communication skills than other programs. Science-Mathematic program had a higher mean score of interpersonal, problem solving and management skills than other programs. (3) The normalize of life and career skills in local level ranged from 49-92 score and normalize T-score ranged from T21-T78. The score of life and career skills for all factors (communication, interpersonal, problem solving and management) ranged from 10-24 score and normalize T-score ranged from T19.89-T74.94. The score of life and career skills by gender, male students got a score ranging from 69-92 and normalize T-score ranged from T23.22-T72.89, while female students got a score between 49-92 and normalize T-score ranged from T21.06-T72.89. The score of life and career skills was summarized all factors by gender; male students got a score ranging from 12-24 and normalize T-score ranged from T23.22-T74.37 while female students got a score between 10-24 and normalize T-score ranged from T21.06-T75.27.